2018
DOI: 10.1158/1535-7163.mct-17-0591
|View full text |Cite
|
Sign up to set email alerts
|

NEO212 Inhibits Migration and Invasion of Glioma Stem Cells

Abstract: Glioblastoma multiforme is a malignant brain tumor noted for its extensive vascularity, aggressiveness, and highly invasive nature, suggesting that cell migration plays an important role in tumor progression. The poor prognosis in GBM is associated with a high rate of tumor recurrence, and resistance to the standard of care chemotherapy, temozolomide (TMZ). The novel compound NEO212, a conjugate of TMZ and perillyl alcohol (POH), has proven to be 10-fold more cytotoxic to glioma stem cells (GSC) than TMZ, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Theories underlying glioma evolution, treatment resistance, and recurrence support the existence and key roles of glioma stem cells (GSCs) [5]. Our study of disordered genes in GSCs may therefore provide possible treatment targets for glioma molecular therapy [6].…”
Section: Introductionmentioning
confidence: 81%
“…Theories underlying glioma evolution, treatment resistance, and recurrence support the existence and key roles of glioma stem cells (GSCs) [5]. Our study of disordered genes in GSCs may therefore provide possible treatment targets for glioma molecular therapy [6].…”
Section: Introductionmentioning
confidence: 81%
“…GBM cells often acquire resistance to TMZ through mutations in the DNA repair mechanisms such as the base excision repair (BER), poly(ADP-ribose) polymerase (PARP), mismatch repair (MMR), and especially, through the overexpression of the repair enzyme O 6 -methyl-guanine-DNA methyltransferase (MGMT) [ 2 ]. One of the main causes for tumor recurrence is a small sub-population of TMZ-resistant glioma stem cells (GSC), with capacity for self-renewal and in vivo tumor initiation [ 3 , 4 ].…”
mentioning
confidence: 99%
“…We have recently reported that NEO212 also decreases migration and invasion of several patient-derived GSC to a greater extent than TMZ and/or POH, through a mechanism independent of its DNA alkylating effects [ 2 ]. TMZ loses its cytotoxicity after 2 h when incubated in cell-free medium at 37°C, while NEO212 loses it after 24 h [ 8 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations